ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦ä¸æ–‡ç³»2012çº§å¦ç”ŸæŽŒæ¡ä»‹è¯â€œæŠŠâ€æƒ…å†µåˆ†æž - Nurchafipah, .; Thamrin, Lily; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
æ‘˜è¦ï¼šæœ¬ç ”ç©¶çš„ç›®çš„æ˜¯ä¸ºäº†è§£ä¸¹å¤§ä¸æ–‡ç³»å¦ç”Ÿå¦ä¹ ä»‹è¯â€œæŠŠâ€å—å¥çš„è¯æ³•æƒ…å†µå’Œéš¾ç‚¹ã€‚ç ”ç©¶å¯¹è±¡æ˜¯ä¸¹å¤§ä¸æ–‡ç³»2012çº§çš„å¦ç”Ÿï¼Œå…±æœ‰35åï¼ˆå¥³ç”Ÿ27åï¼Œç”·ç”Ÿ8åï¼‰ã€‚æ ¹æ®æœ¬æ–‡çš„ç ”ç©¶ç›®çš„ï¼Œç¬”è€…ä¸»è¦åˆ†æžå¦ç”ŸæŽŒæ¡â€œæŠŠâ€å—å¥çš„æƒ…å†µä¸Žéš¾ç‚¹ï¼Œå› æ¤ç¬”è€…ä½¿ç”¨æµ‹éªŒç ”ç©¶æ³•ä¸ºäº†èŽ·å¾—æ›´å¥½çš„è°ƒæŸ¥ç»“æžœã€‚é€šè¿‡ä¸Šè¿°çš„æµ‹è¯•ç»“æžœå¯å¾—çŸ¥ï¼Œä¸¹å¤§ä¸æ–‡ç³»2012 çº§å¦ç”Ÿåœ¨æŽŒæ¡â€œæŠŠâ€å—å¥çš„æƒ…å†µä¸æ˜¯ç‰¹åˆ«ç†æƒ³ï¼Œè¿˜å˜åœ¨ä¸€äº›é—®é¢˜ã€‚ Â  å…³é”®è¯ï¼šè¯æ³•ï¼Œ â€œæŠŠâ€ä»‹è¯æƒ…å†µ Â éš¾ç‚¹ Abstract : The purpose ofÂ thisÂ researchÂ was to know theÂ conditions andÂ difficulties in understandingÂ grammar,Â especially on the prepositionÂ "ba". InÂ this case,Â the objectÂ of the research was students ofÂ Mandarin in Tanjungpura University, year of enrollment 2012. There were 35Â studentsÂ (27Â women andÂ 8Â men). According to the results of the purpose is want to analysis the conditions and difficulties of student,Therefore the method use a method of test ,like make sentence and arrange the sentence. For better, use results of investigation. By the above described test results can be learned, the conditions of prepositions â€œbaâ€ in Chinese tanjungpura university students is not particularly desirable, still there are some problems. Â  Key words: grammar, difficult and the condition understanding â€œbaâ€